2017
DOI: 10.1371/journal.pone.0185562
|View full text |Cite
|
Sign up to set email alerts
|

In vitro chlorhexidine release from alginate based microbeads for periodontal therapy

Abstract: Periodontitis is one of the most common infectious diseases globally that, if untreated, leads to destruction of the tooth supporting tissues and finally results in tooth loss. Evidence shows that standard procedures as mechanical root cleaning could be supported by further treatment options such as locally applied substances. Due to gingival crevicular fluid flow, substances are commonly washed out off the periodontal pockets. The evaluation of administration techniques and the development of local drug relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…To mimic release kinetics in in vitro assays, in most cases the controlled release device is placed in defined, constant volumes over time [35][36][37]. In order to simulate the clinical situation as closely as possible, a GCF flow during a periodontal therapy with decreasing volumes [11] was simulated.…”
Section: Discussionmentioning
confidence: 99%
“…To mimic release kinetics in in vitro assays, in most cases the controlled release device is placed in defined, constant volumes over time [35][36][37]. In order to simulate the clinical situation as closely as possible, a GCF flow during a periodontal therapy with decreasing volumes [11] was simulated.…”
Section: Discussionmentioning
confidence: 99%
“…Periocol-CG releases chlorhexidine in vitro with a release profile of approximately 40-45% within 24 hours and thereon in a linear fashion for 7-8 days. The release profile may be explained as initial burst effect, due to diffusion of the drug from the chip followed by release of the drug due to enzymatic degradation [21].…”
Section: Discussionmentioning
confidence: 99%
“…CHX-containing gels exhibited selective antibacterial effects against the growth of P. gingivalis . CHX was also loaded into alginate-based microparticles and the authors have demonstrated that a higher amount of CHX was released from these microparticles in comparison with PLGA microparticles having the same particle size [ 86 ].…”
Section: Polymer–drug Systemsmentioning
confidence: 99%